The financial performance and corporate governance disclosure: A study in the annual reports of listed companies of Bangladesh - Md. Abdur Rouf (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2012)
This research aims to test empirically the relationship between the Financial Performances (Profitability) and the level of Corporate Governance Disclosure (CGD) by the listed non-financial companies in Bangladesh. Data are taken from annual reports of the listed companies in the 2007. This paper is based on a sample of 94 listed companies and Used OLS as a method of estimation. The extent of corporate governance disclosure level is measured using 40 items of information and financial performance (profitability) is measured by return on assets (ROA). Using an unweighted approach for measuring corporate governance disclosure, this approach is most appropriate when no importance is given to any specific user-groups. After establishing the disclosure index, a scoring sheet was developed to assess the extent of corporate governance disclosures. The result shows that the level of Corporate Governance Disclosure (CGD) is positively correlated with the Financial Performances (Profitability).The study provides empirical evidence to policy makers and regulators in South Asia.
Keywords: 330; Profitability; Corporate Governance Disclosure; Return on Assets; Rentabilität; Corporate Governance; Normbefolgung; Kleinste-Quadrate-Methode; Bangladesch